The Effectiveness of Livable Housing Program: A Case Study of Pidie District of Aceh Province. Issue 1 (June 2021) - Suheri,; Saidi, T; Sugiarto, S
Abstract: A livable house construction program was implemented for the poor by the governments of Pidie district and Aceh province to improve the welfare of the people. These programs were, however, observed not to be effective in achieving the targeted objectives. Therefore, this research was conducted to determine the effectiveness of the decent housing assistant program implemented by the government of Aceh province and Pidie district in 2019 and 2020. This involved the application of the effectiveness analysis through four variables of input, output, outcome, and impact using modified Dantes formula with five achievement levels. Findings from this work is related to effectiveness of the livable house construction programs implemented in Pidie Regency were used to draw the following conclusions: (a) The Aceh provincial government program was analyzed using four variables and found to be effective. The input and output variables were recorded to be quite effective while the outcome and impact variables were less effective; (2) the Pidie regency government program was also analyzed using four variables and found to be less while the input was discovered to be quite effective while the output, outcome, and impact were less effective.